2009
DOI: 10.3141/2130-17
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Work Zone Capacity Values in a Simulation Model

Abstract: Evaluating the traffic impacts of work zones is vital for any transportation agency to plan and schedule work activity. Traffic impacts can be estimated by using microscopic simulation models. One challenge in using these software models is obtaining the desired work zone capacity values, which tend to vary from state to state. Thus, the default parameter values in the model that are suitable for normal traffic conditions are unsuitable for work zone conditions, let alone for conditions specific to particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Since traffic composition and driver characteristics were controlled in both configurations, the detected differences between CLM and JLM would be attributed to the merging behavior, which is the main focus of this analysis. This is consistent with the general application of simulation models to what-if scenarios or the particular application to similar work-zone studies demonstrated by Beacher et al (2005a), Chatterjee et al (2009), Pesti et al (2008, Wei et al (2008), and Yang et al (2009), to name a few. Since JLM is in an experimental stage, the use of simulation provides an insight of its anticipated performance before implementation takes place.…”
Section: Validation Of Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Since traffic composition and driver characteristics were controlled in both configurations, the detected differences between CLM and JLM would be attributed to the merging behavior, which is the main focus of this analysis. This is consistent with the general application of simulation models to what-if scenarios or the particular application to similar work-zone studies demonstrated by Beacher et al (2005a), Chatterjee et al (2009), Pesti et al (2008, Wei et al (2008), and Yang et al (2009), to name a few. Since JLM is in an experimental stage, the use of simulation provides an insight of its anticipated performance before implementation takes place.…”
Section: Validation Of Resultssupporting
confidence: 84%
“…As pointed out by Chatterjee et al (2009), the capacity of work zones may vary from one location to another. In VISSIM, the adopted car following algorithm is based on Wiedemann 99 model, which includes 10 parameters (CC0-CC9) that can be modified by the user during the calibration process.…”
Section: Calibration Of Vissimmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous literature showed that in VISSIM the parameters CC0, CC1, CC2, CC4/CC5, and SRF are suited for model calibration of a work zone. Chatterjee et al [15] argued that between the two parameters CC0 and CC1 that determine the safety distance d xsafe = CC0 + CC1 * v (that in turn determines ISRN Civil Engineering capacity) only CC1 has a significant effect on the safety distance. According to the same study, it was concluded from visual interpretation that CC4/CC5 pair less than 3 resulted in unstable car following process and values higher than 3.0 did not result in variation of the MOE.…”
Section: Driver Behavior Parameter Selection and Calibrationmentioning
confidence: 99%
“…This factor also depends on the number of remaining free lanes: the higher the number of lanes, the smaller the overall effect (i.e., the higher the ). Merging effects and the impact of lane changes have been studied in freeway environments, either with an endogenous model [43][44][45], simulation [46,47], or empirical data [48,49]. In this paper, as it will be later shown, the parameter can be easily calibrated with a simple simulation experiment performed in a controlled manner.…”
Section: Formulationsmentioning
confidence: 99%